Ethics in the research process - Gutiérrez Gómez, Edgar (2020)
The current circumstances further merit investment in scientific research, to contribute to the homogeneous sustainability of the world population. The economic resources destined to the research field must be prioritized in order to rediscover what nature holds for the future man. Practical sumptuousness has plunged humanity into a minimalist idea of ??its social condition. The world phenomena of diverse nature are sneaked by a small group of research philanthropists without state economic funds, absolutely relegated by private companies that profit from raw materials.